Revelation of New Compound from Ethanolic Extract of Fragaria x ananassa var. Lembang - Andayani, Desak Gede Sri; Lotulung, Puspa Dewi Narrij; Sulaswaty, Anny; Qaanitaati, Nur; Andini, Desak Gede Tirta; Mulyani, Rahmaniar; Nursyifa, Eva (Indonesian Society for Cancer Chemoprevention, 2019)
Fragaria x ananassa (strawberry) is a subtropical plant that can adapt well in tropical highlands. Fragaria x ananassa have been widely used to cope with health problems. The active compound component of secondary metabolites contained in Fragaria x ananassa has the potential as an antioxidant. This research is done to isolate secondary metabolites from extract of Fragaria x ananassa fruits. Extract Fragaria x ananassa was produced by maceration using ethanol as the solvent. Separation and isolation compound were carried out using Vacuum Liquid Chromatography (VLC) and Gravity Column Chromatography (GCC) guided by Thin Layer Chromatography (TLC) using hexane: ethyl acetate (3:7) as the eluent. The flavonoid compound was determined by the total content of phenolic and flavonoid in extract of Fragaria x ananassa fruits. The results of total phenolic content and total flavonoid content were 0.1130 mg/g and 0.0112 mg/g, respectively. The alkaloid compound was determined by Dragendorff testing. The elucidation of the structure by Fourier Tansform Infrared (FTIR), Nuclear Magnetic Resonance (NMR), and Liquid Chromatography Mass Spectrometry (LCMS) showed that the active compound contained in the secondary metabolite of extract ethanol from Fragaria x ananassa is 3-Cyclopentyl-5-(1-hydroxyethyl)-1,6-dihydro-7H-pyrazolo[4,3- d]pyrimidin-7-one.Keywords: Fragaria x ananassa extract, flavonoid, alkaloid, total phenolic and flavonoid content, FTIR, NMR, LCMS.